An Immunological Approach to Postpericardiotomy Syndrome Occurrence and Its Relation with Autoimmunity - (:unkn) unknown (My University, 1998)
Objective : An autoimmunological approach to the pathogenesis of post-pericardiotomy syndrome. Methods : In 100 consecutive patients, after open heart surgery, postpericardiotomy syndrome (PPS) was diagnosed in 15 patients according to clinical and laboratory criteria. These patients were prospectively followed up. Levels of serum autoantibodies against cardiac muscle antigen were studied on the 14th, 21st and 33rd day postoperatively. In order to evaluate the cardiac muscle antibody (CMA), antigenic tissue sections from primate heart tissue in solid phase with intermyofibrillar and sarcolemmal-subsarcolemmal fluorescent staining, were taken as substrate. PPS occurrence was determined according to strongly positive antibody titers on the 14th and 21st day postoperatively. Results : CMA were positive in 18 patients, and 14 of them showed clinical signs of PPS. In one case PPS was apparent clinically although CMA were not detected. There was a significant difference between CMA positive and CMA negative patients on the occurrence of PPS. With the use of monoclonal antihuman IgG in the conjugate of indirect fluorescent antibody test the specificity was enhanced. Also, in our experience, the length of cardiopulmonary bypass (CPB) time was an important factor affecting the development of PPS. Conclusion : In this study, we found a positive correlation between the presence of CMA and PPS, which is a practical, secure and cheap criterion for the diagnosis.
Keywords: Autoimmunity; Open heart surgery; Postpericardiotomy syndrome